Mechanism of Metachromasy Induced by the Binding of Dissociated and Undissociated Bromocresol Purple to Separate Sites on Human Serum Albumin - Ito, Shigenori (Current Pharmaceutical Analysis, 2016)
Background: The color-change mechanism of bromocresol purple (BCP) bound to a human serum albumin (HSA) molecule can be explained via the following proton-exchange reactions: (i) BCP- + HSA-COO- → BCP2- + HSA-COOH (pH < 6.0; i.e., the pKa of BCP-) and (ii) BCP2- + HSANH3+ → BCP- + HSA-NH2 (pH > 6.0). These can be monitored through pH-dependent experiments and are consistent with the absorbance data calculated using the Henderson-Hasselbalch equation. Methods: The absorbance spectra of the BCP-HSA complex were measured over a range of pH values (2.4–11.6) and HSA concentrations (0–25.6 μmol/L). Results: Six peaks were observed in the absorbance spectra. The HSA-concentration-dependent absorbance change at 430 nm (attributed to BCP) decreased with a simultaneous increase in absorbance at 599 nm at a pH lower than 6.0; the absorbance at 584 nm (attributed to BCP2-) decreased with a simultaneous increase in absorbance at 613 nm at a pH higher than 6.0. The peaks at 599 and 613 nm did not correspond to BCP2- and BCP. Conclusion: The structures of the BCP2- and BCP produced are stabilized by resonance-assisted hydrogen bonds, and reverse reactions do not occur in the two separate (BCP- and BCP2-) binding sites.
Keywords: color-change mechanism